Author`s methodology for the express testing of combat athletes from the Kazakhstan Olympic WKF karate team - Sanauov, Z.; Boldyrev, B. (Journal of Physical Education and Sport, 2020)
The purpose of this study is to develop an effective method of express testing to correct the functionality and to stabilize the performance of member athletes from the national World Karate Federation (WKF) karate team of the Republic of Kazakhstan (RK) during training and competition activities. When forming the author`s express testing methodology, to control the functionality of karate athletes using the latest generation of heart rate monitors, the authors for the first time in Kazakhstan developed a methodology for testing combat athletes practicing WKF karate and prepared recommendations for using the sum of heart rate figures as a factor reflecting the objective amount of functional exertion of karate athletes to stabilize athlete performance. The obtained data show that the innovative method declared by the authors, which describes the functioning of the training process through the creation of digital databases, allows to more objectively coordinatethe methods of training athletes to participate in the most important sports events including the Olympics.